The Effect of the Discretization Process on Fibber Quality Indicators - Jamshid Yuldashev; Sardor Tojimurotov (Genius Journals, 2023)
In this article, a practical analysis of the mechanical impact of the discretizing of a pneumo-mechanical spinning machine on the fibres of the fed skein is made. The degree of mechanical damage to the fibre at different speeds of the discrete drum was studied on a HVI machine and a histogram was built based on the results obtained. The constructed histogram was analysed and alternative values were determined.
Keywords: maturity; fibre; vacuum